2015
DOI: 10.1017/s0007485315000243
|View full text |Cite
|
Sign up to set email alerts
|

Surviving a flood: effects of inundation period, temperature and embryonic development stage in locust eggs

Abstract: The Australian plague locust, Chortoicetes terminifera (Walker), is an important agricultural pest and oviposits into compacted soil across vast semi-arid and arid regions prone to irregular heavy summer rainfall. This study aimed to quantify the effects of flooding (control, 7, 14, 21, 28 and 35 days) at different temperatures (15, 20 and 25°C) and embryonic development stages (25 and 75%) on egg viability, hatchling nymph body mass and survival to second-instar. Egg viability after flooding was dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The insect survival is not only associated with immersion period, but also insect density and amount of water in water immersion environment [35,36]. We investigated the effect of immersion period on the survival of citrus large fruit fly larvae, and the larval density and water content need to be further studied…”
Section: Discussionmentioning
confidence: 99%
“…The insect survival is not only associated with immersion period, but also insect density and amount of water in water immersion environment [35,36]. We investigated the effect of immersion period on the survival of citrus large fruit fly larvae, and the larval density and water content need to be further studied…”
Section: Discussionmentioning
confidence: 99%
“…A study was done and showed that heavy rainfalls can result to high rates of locust mortality. Heavy rainfalls affected the locusts eggs and the nymph survival was reduced severely (Woodman, 2015).…”
Section: Extreme Weather Eventsmentioning
confidence: 99%
“…Meteorological conditions are the key factors that are related to high-density locust forming. Temperature and precipitation can influence the whole locust cycle, including hatching, spawning, and growing periods [12][13][14]. Therefore, the analysis of high-density locust forming mechanisms should consider both habitat dynamic changes and meteorological conditions.…”
Section: Introductionmentioning
confidence: 99%